ARGUMENTAÇÃO CIENTÍFICA COMO FERRAMENTA CULTURAL NA FORMAÇÃO INICIAL DOCENTE (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
Scientific argumentation is an important teaching knowledge in the initial training of chemistry teachers. In this article, we collected data from undergraduates in chemistry from a public university in the interior of the state of São Paulo that show important aspects about the elaboration of meanings with scientific argumentation. Data were collected in the form of a questionnaire and interviews with participants one year after coming into contact with the topic, and before resuming the topic and applying it to supervised curricular internships. Data organization was based on Discursive Textual Analysis (DTA) using Toulmin's conceptions (TAP) as a priori categories. In the analysis of the results, we start from the sociocultural conceptions of mastery of cultural tools. The data evidenced the possibility that the undergraduates showed mastery of TAP in solving theoretical argumentative activities and at the same time did not master the theoretical aspects of TAP. The data also confirm other elements already present in the literature, such as the importance of TAP being linked to scientific content and also the improvement of results when students elaborate their arguments orally, compared to written arguments.
Keywords: Initial teacher training; scientific argumentation; sociocultural approach; chemistry education